TRANSFORMING CODE: EVALUATING THE IMPACT OF GENERATIVE AI ON SOFTWARE ENGINEERING PRODUCTIVITY (Multidisciplinary Journal of Science and Technology, 2026)
The integration of Generative Artificial Intelligence (GenAI) into the software development life cycle is fundamentally reshaping traditional programming paradigms. This paper evaluates the empirical impact of GenAI tools on software engineering productivity, code quality, and development velocity. Employing a mixed-methods research design, we analyzed quantitative performance metrics from 150 software engineers alongside a comprehensive literature review of recent case studies. The empirical results demonstrate that AI assistance accelerates routine coding tasks and boilerplate generation by up to 45%, significantly reducing time-to-market. However, the findings also reveal critical bottlenecks, including a 15% increase in code review duration due to potential AI hallucinations and security vulnerabilities. Ultimately, this study suggests that while GenAI dramatically enhances individual developer throughput, human oversight remains indispensable to maintain architectural integrity and security standards.